The role of the ICT teacher in e-learning-based teaching - Sukisworo, Fetri; Marsono, Marsono; Widiyanti, Widiyanti (Technium Social Sciences Journal, 2021)
The Covid-19 pandemic has had a fundamental impact on various aspects of humanity. Starting from attacking health, this pandemic has hit the education sector which is quite influential on human life. Enforcement of regulations while maintaining a distance of about one meter has implications for the education process in Indonesia. Therefore, the educational element must encourage the distance learning process. The term arises because it sees distance learning as an alternative to face-to-face methods so that education can always be held without controversy under any circumstances. This activity raises the use of technology that is used as teaching material for distance education. Distance learning techniques allow users to take advantage of technologies such as online learning. Teachers will be required to abandon using traditional techniques whose methods are somewhat indifferent. Online learning creates internet connectivity and the use of information technology in helping the teaching and learning process that can be applied in Google Classroom. In this article, researchers focus on using Google Classroom in the context of implementing distance learning during the Covid-19 pandemic.